Pharmaceutical company spending on research and development and promotion in Canada, 2013-2016: a cohort analysis - Joel Lexchin (Taylor & Francis Group, 2018)
Background Competing claims are made about the amount of money that pharmaceutical companies spend on research and development (R&D) versus promotion. This study investigates this question in the Canadian context. Methods Two methods for determining industry-wide figures for spending on promotion were employed. First, total industry spending on detailing and journal advertising for 2013-2016 was abstracted from reports from QuintilesIMS. Second, the mean total promotion spending for the years 2002-2005 was used to estimate total spending for 2013-2016. Total industry spending on R&D came from the Patented Medicine Prices Review Board (PMPRB). R&D to promotion spending using each method of determining the amount spent on promotion was compared for 2013-2016 inclusive. Data on the 50 top promoted drugs, the amounts spent, the companies marketing these products and their overall sales were abstracted from the QuintilesIMS reports. Spending on R&D and promotion as a percent of sales was compared for these companies. Results Industry wide, the ratio of R&D to promotion spending went from 1.43 to 2.18 when promotion was defined as the amount spent on detailing and journal advertising for the 50 most promoted drugs. Calculating total promotion spending from the mean of the 2002-2005 figures the ratio was 0.88 to 1.32 for the 50 most promoted drugs. For individual companies marketing one or more of the 50 most promoted drugs, mean R&D spending ranged from 3.7% of sales to 4.1% compared to mean promotion spending that went from 1.7 to 1.9%. The ratio of spending on R&D to promotion varied from 2.11 to 2.32. Eight to 10 companies per year spent more on promotion than on R&D. Conclusions Depending on the method used to determine promotion spending, industry-wide the ratio of R&D spending to promotion ranges from 1.45 to 2.18 (sales representatives and journal advertising only) or from 0.88 to 1.32 (total promotion spending estimated based 2003-2005 data.) For the individual companies promoting one or more of the 50 most promoted drugs, 2.11 to 2.32 times more is spent on R&D compared to promotion. However these results should be interpreted cautiously because of data limitations.